Artemia spp., a Susceptible Host and Vector for Lymphocystis Disease Virus. - Jiménez Valverde, Estefanía; Labella Vera, Alejandro Manuel; Borrego-García, Juan José; Castro-López, María Dolores (MDPI, 2019)
Di erent developmental stages of Artemia spp. (metanauplii, juveniles and adults) were bath-challenged with two isolates of the Lymphocystis disease virus (LCDV), namely, LCDV SA25 (belonging to the species Lymphocystis disease virus 3) and ATCC VR-342 (an unclassified member of the genus Lymphocystivirus). Viral quantification and gene expression were analyzed by qPCR at di erent times post-inoculation (pi). In addition, infectious titres were determined at 8 dpi by integrated cell culture (ICC)-RT-PCR, an assay that detects viral mRNA in inoculated cell cultures. In LCDV-challenged Artemia, the viral load increased by 2–3 orders of magnitude (depending on developmental stage and viral isolate) during the first 8–12 dpi, with viral titres up to 2.3 102 Most Probable Number of Infectious Units (MPNIU)/mg. Viral transcripts were detected in the infected Artemia, relative expression values showed a similar temporal evolution in the di erent experimental groups. Moreover, gilthead seabream (Sparus aurata) fingerlings were challenged by feeding on LCDV-infected metanauplii. Although no Lymphocystis symptoms were observed in the fish, the number of viral DNA copies was significantly higher at the end of the experimental trial and major capsid protein (mcp) gene expression was consistently detected. The results obtained support that LCDV infects Artemia spp., establishing an asymptomatic productive infection at least under the experimental conditions tested, and that the infected metanauplii are a vector for LCDV transmission to gilthead seabream.
Keywords: Peces - Enfermedades por virus; Lymphocystis disease virus; Artemia spp; Sparus aurata; Viral transmission